Complex-phase lithium-rich positive electrode material as well as preparation method and application thereof

A multi-phase lithium-rich positive electrode material, combining lithium-rich manganese-based and spinel components, addresses the balance of high energy density and long service life, enhancing battery performance through particle grading and high-energy ball milling.

CN119208569APending Publication Date: 2024-12-27NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411358904.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing lithium-rich positive electrode materials struggle to balance high energy density with long service life, failing to meet the stringent requirements of modern devices.

Method used

A multi-phase lithium-rich positive electrode material composed of lithium-rich manganese-based and partially ordered lithium-rich spinel materials, prepared through high-energy ball milling, achieving a specific mass ratio and particle grading to enhance energy storage density and service life.

Benefits of technology

The composite material system exhibits improved energy storage density and extended service life, demonstrating enhanced specific capacity and tap density, suitable for high-performance lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208569A_ABST
    Figure CN119208569A_ABST
Patent Text Reader

Abstract

The invention discloses a complex-phase lithium-rich positive electrode material as well as a preparation method and application thereof, belongs to the technical field of battery positive electrode materials, and solves the problem that a material in the prior art cannot meet the requirements of high energy density and long service life at the same time. The complex-phase lithium-rich positive electrode material provided by the invention comprises the following components: a lithium-rich manganese-based positive electrode material and a partially ordered lithium-rich spinel positive electrode material in a mass ratio of (1-20): 1, wherein the particle size of the lithium-rich manganese-based positive electrode material is 1-20 [mu] m, and the particle size of the partially ordered lithium-rich spinel positive electrode material is 50-500 nm. The complex-phase lithium-rich positive electrode material provided by the invention is used as a battery positive electrode active material, and the energy storage density and the service life of the battery are improved in multiple dimensions from the aspects of improving the specific capacity through cooperation of anions and cations, improving the tap density through particle size grading fusion and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery positive electrode materials, and more specifically to a multi-phase lithium-rich positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, energy storage grids and other fields due to their high energy density, long cycle life, low self-discharge and portability. At the same time, the endurance anxiety caused by the rapid power loss of electronic devices and the range anxiety caused by the short driving range of electric vehicles have put forward higher requirements on the energy density of lithium-ion batteries.

[0003] Lithium-rich manganese-based cathode materials (Li 1+x M 1-x O2, where M is Mn, Ni, Co, etc. or any combination thereof, 0≤x≤1) due to its high capacity of 250mAh·g -1 With a reversible specific capacity of 1000 Wh kg and an operating voltage of 4.8 V, its energy density can reach 1000 Wh kg -1 (vs.Li / Li + ), far exceeding the ternary layered cathode materials and lithium iron phosphate cathode materials that have been commercially applied, and it has a relatively good cycle life. In addition, the cost is low because the amount of expensive cobalt and nickel elements is reduced. At the same time, thanks to the reduction in the content of nickel elements, its safety performance is improved. These advantages make lithium-rich manganese-based cathode materials as candidate cathode materials for high-performance lithium-ion batteries, with good development prospects. However, because excessive lithium ions are inserted into the bulk lattice and the amount of transition metal ions is reduced, the intrinsic density of the material is reduced, which in turn causes the material's tap density to decrease, and ultimately leads to a significant decrease in volume energy density. In addition, the specific capacity of existing lithium-rich manganese-based cathode materials has reached its upper limit, and it is difficult to meet the stringent requirements of new devices in terms of energy density and other aspects.

[0004] Partially ordered lithium-rich spinel cathode materials (Li 1.4+y Mn 1.6 O 4-z F z ) is a new generation of high-capacity cathode material between the ordered spinel phase and the disordered rock salt phase. On the basis of retaining the spinel structure, the disordered rock salt structure inhibits the phase transition reaction of the ordered spinel material and is beneficial to the redox of oxygen, which can further increase the specific capacity of the material. Therefore, it shows a high specific capacity of up to 363mAh·g -1 The reversible specific capacity and excellent rate performance (20A·g -1 At a current density of 1000 Wh kg -1 , vs.Li / Li +Ultra-high energy density) and is expected to become a candidate positive electrode material for the next generation of high energy density and high power density batteries. However, its reversible charge and discharge specific capacity decays severely, making it difficult to meet the stringent requirements of new devices in terms of service life.

[0005] Therefore, existing lithium-rich positive electrode materials cannot combine high energy density, excellent kinetics and excellent capacity stability, and cannot meet the requirements for energy density and service life of lithium-ion batteries. Summary of the invention

[0006] The present invention provides a multi-phase lithium-rich positive electrode material and a preparation method and application thereof, so as to solve the problem that the materials in the prior art cannot have both high energy density and long service life.

[0007] In the first aspect, the present invention provides a multiphase lithium-rich positive electrode material, comprising the following components: a lithium-rich manganese-based positive electrode material and a partially ordered lithium-rich spinel positive electrode material in a mass ratio of 1 to 20:1; wherein the particle size of the lithium-rich manganese-based positive electrode material is 1 to 20 μm, and the particle size of the partially ordered lithium-rich spinel positive electrode material is 50 to 500 nm.

[0008] As a possible implementation method, the lithium-rich manganese-based positive electrode material is Li 1+x M 1-x O2, wherein M is one or a combination of Mn, Ni, and Co, and 0≤x≤1; the partially ordered lithium-rich spinel positive electrode material is Li 1.4+ y Mn 1.6 O 4-z F z , among which, 0.07≤y≤0.6, 0.3≤z≤0.6.

[0009] In a second aspect, the present invention provides a method for preparing a composite lithium-rich positive electrode material as described in any possible implementation of the first aspect, wherein the raw material components are mixed in proportion according to the formula components contained in the composite lithium-rich positive electrode material as described in any possible implementation of the first aspect, and high-energy ball milling operation is performed to obtain the composite lithium-rich positive electrode material.

[0010] As a possible implementation method, the high-energy ball milling is dry milling or wet milling with anhydrous ethanol as solvent; and / or, the conditions of the high-energy ball milling are a rotation speed of 100 to 600 rpm and a duration of 2 to 24 hours; and / or, the ball-to-material ratio of the high-energy ball milling is 1.5 to 25:1.

[0011] As a possible implementation method, the preparation process of the lithium-rich manganese-based positive electrode material includes the following steps: dissolving the M source in pure water, adding Na2CO3 solution, adding a pH adjuster to adjust the pH to 7.5-9, stirring for 4-24 hours in an oxygen-free atmosphere, filtering the precipitate, washing, drying, and grinding in sequence to obtain a carbonate precursor, wherein the M source is one or a combination of a nickel source, a cobalt source, and a manganese source; mixing the carbonate precursor and a lithium source, pre-sintering at 400-600°C, sintering at 700-900°C, and cooling to room temperature to obtain the lithium-rich manganese-based positive electrode material.

[0012] As a possible implementation, the pH adjuster includes one of ammonia water and ammonium bicarbonate or a combination of the two; and / or the oxygen-free atmosphere is a nitrogen atmosphere or an argon atmosphere; and / or the drying conditions are: temperature 100-150°C, time 12-24h; and / or the pre-sintering time is 4-8h; and / or the sintering time is 6-18h.

[0013] Exemplarily, after the M source is dissolved in pure water, a mixed solution is obtained, and the molar concentration ratio of the Na2CO3 solution and the mixed solution is 1:2.

[0014] As a possible implementation method, the nickel source is one or a combination of Ni(CH3COO)2·4H2O, NiSO4 and Ni(NO3)2·6H2O; the cobalt source is one or a combination of Co(CH3COO)2·4H2O, CoSO4 and Co(NO3)2·6H2O; the manganese source is one or a combination of Mn(CH3COO)2·4H2O, MnSO4 and Mn(NO3)2·4H2O; the lithium source is one or a combination of LiOOCCH3, Li2CO3, LiNO3 and LiOH·H2O.

[0015] Exemplarily, the preparation process of the partially ordered lithium-rich spinel positive electrode material includes the following steps: in terms of the amount of substance, a lithium source and a manganese source with a ratio of lithium element to manganese element of 2.05 to 2.10 are mixed with anhydrous ethanol as a solvent and ball-milled for 1 to 8 hours, dried, and calcined at 700 to 900° C. for 4 to 12 hours to obtain Li2MnO3; according to the molecular formula Li 1.4+y Mn 1.6 O 4-z F z , the reaction precursors of corresponding stoichiometric ratios are mixed and ball-milled, wherein the ball-to-material ratio is 10 to 25:1, and the mixture is ball-milled at a rotation speed of 350 to 850 rpm for 15 to 30 hours under an inert atmosphere to obtain the partially ordered lithium-rich spinel positive electrode material.

[0016] As a possible implementation, the lithium source is one or a combination of LiOOCCH3, Li2CO3, LiNO3 and LiOH·H2O; and / or the manganese source is one or a combination of Mn(CH3COO)2·4H2O, MnSO4, Mn(NO3)2·4H2O or MnO2; and / or the inert atmosphere is argon or nitrogen; and / or the reaction precursor consists of A, B, C and D, wherein A is Li2MnO3, B is one or a combination of MnF2, MnO and Mn(OH)2, C is one or a combination of Mn2O3 and MnF3, and D is MnO2.

[0017] In a third aspect, the present invention provides an application of the multiphase lithium-rich positive electrode material described in any possible implementation of the first aspect or the multiphase lithium-rich positive electrode material prepared by the preparation method described in any possible implementation of the second aspect in a lithium-ion battery.

[0018] In a fourth aspect, the present invention provides a lithium-ion battery, using the composite lithium-rich positive electrode material described in any possible implementation of the first aspect or the composite lithium-rich positive electrode material prepared by the preparation method described in any possible implementation of the second aspect as its positive electrode active material.

[0019] As a possible implementation method, the preparation process of the positive electrode includes the following steps: mixing the multi-phase lithium-rich positive electrode material described in any possible implementation method of the first aspect or the multi-phase lithium-rich positive electrode material prepared by the preparation method described in any possible implementation method of the second aspect, conductive agent black and solvent, and then coating them on the current collector, and drying them to obtain the positive electrode of the lithium-ion battery.

[0020] The multi-phase lithium-rich positive electrode material provided by the present invention realizes the particle grading of the lithium-rich manganese-based positive electrode material and the partially ordered lithium-rich spinel positive electrode material at a specific mass ratio, thereby synergistically improving the energy storage density and service life of the battery.

[0021] The present invention adopts controllable multi-stage high-energy ball milling technology to prepare a nano-spinel positive electrode with adjustable order, and realizes its integrated enhancement of the lithium-rich manganese-based positive electrode through a one-step mechanochemical composite, forming an ultra-high specific capacity composite positive electrode material system with phase composite and particle grading, which improves the energy storage density and service life of the battery in multiple dimensions from the aspects of synergistic improvement of specific capacity by anions and cations and improvement of tap density by fusion of particle size grading.

[0022] The preparation method of the present invention has a simple process flow, low cost, and is easy to mass produce, and can promote the development and industrial application of ultra-high energy density lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 Schematic diagram of the preparation principle of the multi-phase lithium-rich positive electrode material provided in an embodiment of the present invention.

[0025] Figure 2 This is a SEM image of the multiphase lithium-rich positive electrode material A prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In order to solve the problem that the materials in the prior art cannot meet the requirements of both high energy density and long service life, an embodiment of the present invention provides a preparation experiment of a multi-phase lithium-rich positive electrode material, and verifies through SEM analysis that the target product is prepared by the present invention. Figure 1 Schematic diagram of the preparation principle of the multiphase lithium-rich positive electrode material provided in the embodiment of the present invention, comprising Figure 1 It can be seen that the multi-phase lithium-rich positive electrode material provided by the present invention realizes the particle grading of the lithium-rich manganese-based positive electrode material and the partially ordered lithium-rich spinel positive electrode material at a specific mass ratio, thereby synergistically improving the energy storage density and service life of the battery.

[0028] Furthermore, the present invention provides an electrochemical performance test experiment of a composite lithium-rich positive electrode material, which verifies that the composite lithium-rich positive electrode material provided by the present invention can improve the specific capacity of the positive electrode side of the battery as a positive electrode active material of the battery and has good cycle performance.

[0029] Furthermore, the present invention provides a tap density test experiment of a multi-phase lithium-rich positive electrode material, which verifies that an ultra-high specific capacity composite positive electrode material system with phase composite and particle grading formed by partially ordered lithium-rich spinel positive electrode material and lithium-rich manganese-based positive electrode material can further improve the tap density of the material on the basis of the original lithium-rich manganese-based oxide material.

[0030] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0031] Example 1

[0032] This embodiment provides an experiment for preparing a multi-phase lithium-rich positive electrode material.

[0033] 0.013 mol (2.0119 g) of NiSO4, 0.013 mol (2.0149 g) of CoSO4 and 0.054 mol (8.1541 g) of MnSO4 were mixed and dissolved in pure water to prepare 2 mol·L -1 of transition metal ion solution, add 1 mol·L -1 Na2CO3 solution was added, and ammonia water was added dropwise to adjust the pH to 8. After stirring for 12 hours under a nitrogen atmosphere, the mixture was filtered, the precipitate was taken, and washed with pure water, then dried at 120°C for 12 hours, and ground to obtain a carbonate precursor A. The carbonate precursor A was mixed with 0.06 mol (4.6551 g, 5 wt% excess) of Li2CO3, pre-sintered at 400°C for 6 hours in a muffle furnace, and then secondary sintered at 900°C for 18 hours. After naturally cooling to room temperature, a lithium-rich manganese-based positive electrode material A was obtained.

[0034] 0.105 mol (7.7585 g) of Li2CO3 and 0.1 mol (8.6937 g) of MnO2 were placed in a ball mill, mixed with anhydrous ethanol as a solvent for 2 h, dried, and calcined at 800 ° C in a muffle furnace for 8 h to obtain Li2MnO3. 0.084 mol (7.1247 g) of Li2MnO3, 0.015 mol (1.3940 g) of MnF2, 0.004 mol (0.6315 g) of Mn2O3, and 0.053 mol (4.6077 g) of MnO2 were placed in a ball mill, with a ball-to-material ratio of 20:1 and a rotation speed of 600 rpm, and ball milled for 20 h in an argon atmosphere to obtain a partially ordered lithium-rich spinel positive electrode material A.

[0035] The lithium-rich manganese-based positive electrode material A and the partially ordered lithium-rich spinel positive electrode material A are mixed in a mass ratio of 5:1, and the operation mode of the high-energy ball mill is set to dry grinding, the rotation speed is 300 rpm, the duration is 12 h, the ball-to-material ratio is 10:1, and the ball milling atmosphere is argon to obtain a composite lithium-rich positive electrode material A.

[0036] Example 2

[0037] This embodiment provides an experiment for preparing a multi-phase lithium-rich positive electrode material.

[0038] 0.012 mol (2.9854 g) of Ni(CH3COO)2·4H2O, 0.012 mol (2.9882 g) of Co(CH3COO)2·4H2O and 0.056 mol (13.7217 g) of Mn(CH3COO)2·4H2O were mixed and dissolved in pure water to prepare 3 mol·L -1 of transition metal ion solution, add 1.5 mol·L -1 Na2CO3 solution was added, and ammonia water was added dropwise to adjust the pH to 7.5. After stirring for 4 hours under a nitrogen atmosphere, the mixture was filtered, the precipitate was taken, washed with pure water, and then dried at 100°C for 18 hours and ground to obtain a carbonate precursor B. The carbonate precursor B was mixed with 0.12 mol (5.2857 g, 5 wt% excess) of LiOH·H2O, pre-sintered at 600°C for 4 hours in a muffle furnace, and then secondary sintered at 700°C for 12 hours. After naturally cooling to room temperature, a lithium-rich manganese-based positive electrode material B was obtained.

[0039] 0.205 mol (14.1348 g) of LiNO3 and 0.1 mol (8.6937 g) of MnO2 were placed in a ball mill, mixed with anhydrous ethanol as a solvent for 6 hours, dried, and calcined at 700 ° C in a muffle furnace for 12 hours to obtain Li2MnO3. 0.0735 mol (6.2341 g) of Li2MnO3, 0.035 mol (2.4828 g) of MnO, 0.01 mol (1.1193 g) of MnF3, and 0.073 mol (6.3464 g) of MnO2 were placed in a ball mill, with a ball-to-material ratio of 15:1 and a rotation speed of 850 rpm, and ball milled for 15 hours in a nitrogen atmosphere to obtain a partially ordered lithium-rich spinel positive electrode material B.

[0040] The lithium-rich manganese-based positive electrode material B and the partially ordered lithium-rich spinel positive electrode material B are mixed in a mass ratio of 10:1, and the operation mode of the high-energy ball mill is set to dry grinding, the rotation speed is 600 rpm, the duration is 6 h, the ball-to-material ratio is 20:1, and the ball milling atmosphere is air to obtain a composite lithium-rich positive electrode material B.

[0041] Example 3

[0042] This embodiment provides an experiment for preparing a multi-phase lithium-rich positive electrode material.

[0043] 0.009 mol (2.6163 g) of Ni(NO3)2·6H2O, 0.012 mol (3.4913 g) of Co(NO3)2·6H2O and 0.056 mol (14.0530 g) of Mn(NO3)2·4H2O were mixed and dissolved in pure water to prepare 4 mol·L -1 of transition metal ion solution, followed by the addition of 2 mol·L -1Na2CO3 solution was added, and ammonia water was added dropwise to adjust the pH to 9. After stirring and reacting for 20 hours under a nitrogen atmosphere, the mixture was filtered, the precipitate was taken, and washed with pure water, then dried at 150°C for 6 hours, and ground to obtain a carbonate precursor C. The carbonate precursor C was mixed with 0.123 mol (9.1593 g, 8 wt% excess) of LiNO3, pre-sintered at 400°C for 8 hours in a muffle furnace, and then secondary sintered at 850°C for 14 hours. After naturally cooling to room temperature, a lithium-rich manganese-based positive electrode material C was obtained.

[0044] 0.21 mol (8.8095 g) of LiOH·H2O and 0.1 mol (25.0948 g) of Mn(NO3)2·4H2O were placed in a ball mill, mixed with anhydrous ethanol as a solvent for 8 h, and dried, and calcined at 850°C in a muffle furnace for 8 h to obtain Li2MnO3. 0.084 mol (7.1247 g) of Li2MnO3, 0.024 mol (1.7025 g) of MnO, 0.02 mol (2.2386 g) of MnF3, and 0.032 mol (2.7820 g) of MnO2 were placed in a ball mill, at a ball-to-material ratio of 25:1, at a rotation speed of 750 rpm, and ball milled for 20 h in an argon atmosphere to obtain a partially ordered lithium-rich spinel positive electrode material C.

[0045] The lithium-rich manganese-based positive electrode material C and the partially ordered lithium-rich spinel positive electrode material C are mixed in a mass ratio of 7:1, and the operation mode of the high-energy ball mill is set to wet grinding, the rotation speed is 500 rpm, the duration is 10 h, the ball-to-material ratio is 5:1, and the ball milling atmosphere is nitrogen to obtain a composite lithium-rich positive electrode material C.

[0046] Example 4

[0047] This embodiment provides an experiment for preparing a multi-phase lithium-rich positive electrode material.

[0048] 0.0139 mol (2.1512 g) of NiSO4, 0.0139 mol (4.0440 g) of Co(NO3)2·6H2O and 0.0556 mol (8.3957 g) of MnSO4 were mixed and dissolved in pure water to prepare 2 mol·L -1 of transition metal ion solution, followed by the addition of 1 mol·L -1 Na2CO3 solution was added, and ammonia water was added dropwise to adjust the pH to 8.5. After stirring for 10 hours under a nitrogen atmosphere, the mixture was filtered, the precipitate was taken, and washed with pure water, then dried at 110°C for 12 hours, and ground to obtain a carbonate precursor D. The carbonate precursor D was mixed with 0.1166 mol (8.2330 g, 7 wt% excess) of LiOOCCH3, pre-sintered at 450°C for 7 hours in a muffle furnace, and then secondary sintered at 800°C for 10 hours. After naturally cooling to room temperature, a lithium-rich manganese-based positive electrode material D was obtained.

[0049] 0.21 mol (8.8095 g) of LiOH·H2O and 0.1 mol (15.1001 g) of MnSO4 were placed in a ball mill, mixed with anhydrous ethanol as a solvent for 6 h, dried, and calcined at 800 ° C in a muffle furnace for 10 h to obtain Li2MnO3. 0.1 mol (8.4817 g) of Li2MnO3, 0.015 mol (1.3940 g) of MnF2, 0.02 mol (3.1575 g) of Mn2O3, and 0.005 mol (0.4347 g) of MnO2 were placed in a ball mill, at a ball-to-material ratio of 10:1, a rotation speed of 650 rpm, and ball milled for 18 h in a nitrogen atmosphere to obtain a partially ordered lithium-rich spinel positive electrode material D.

[0050] The lithium-rich manganese-based positive electrode material D and the partially ordered lithium-rich spinel positive electrode material D are mixed in a mass ratio of 6:1, and the operation mode of the high-energy ball mill is set to dry grinding, the rotation speed is 400 rpm, the duration is 12 h, the ball-to-material ratio is 8:1, and the ball milling atmosphere is argon to obtain a high specific capacity composite lithium-rich positive electrode material D.

[0051] Example 5

[0052] This embodiment provides an experiment for preparing a multi-phase lithium-rich positive electrode material.

[0053] 0.013 mol (3.7791 g) of Ni(NO3)2·6H2O, 0.013 mol (2.0149 g) of CoSO4 and 0.054 mol (8.1541 g) of MnSO4 were mixed and dissolved in pure water to prepare 2 mol·L -1 of transition metal ion solution, add 1 mol·L -1 Na2CO3 solution was added, and ammonia water was added dropwise to adjust the pH to 8.5. After stirring and reacting for 18 hours under a nitrogen atmosphere, the mixture was filtered, the precipitate was taken, and washed with pure water, then dried at 140°C for 16 hours, and ground to obtain a carbonate precursor E. The carbonate precursor E was mixed with 0.06 mol (4.6551 g, 5 wt% excess) of Li2CO3, pre-sintered at 400°C for 8 hours in a muffle furnace, and then secondary sintered at 900°C for 18 hours. After naturally cooling to room temperature, a lithium-rich manganese-based positive electrode material E was obtained.

[0054] 0.105 mol (7.7585 g) of Li2CO3 and 0.1 mol (15.1001 g) of MnSO4 were placed in a ball mill, mixed with anhydrous ethanol as a solvent for 6 hours, dried, and calcined at 900 ° C in a muffle furnace for 4 hours to obtain Li2MnO3. 0.084 mol (7.1247 g) of Li2MnO3, 0.015 mol (1.3940 g) of MnF2, 0.004 mol (0.6315 g) of Mn2O3, and 0.053 mol (4.6077 g) of MnO2 were placed in a ball mill, with a ball-to-material ratio of 25:1 and a rotation speed of 350 rpm, and ball milled for 24 hours in an argon atmosphere to obtain a partially ordered lithium-rich spinel positive electrode material E.

[0055] The lithium-rich manganese-based positive electrode material E and the partially ordered lithium-rich spinel positive electrode material E are mixed in a mass ratio of 2:1, and the operation mode of the high-energy ball mill is set to wet grinding, the rotation speed is 450 rpm, the duration is 20 h, the ball-to-material ratio is 1:1, and the ball milling atmosphere is nitrogen to obtain the composite lithium-rich positive electrode material E.

[0056] Example 6

[0057] This embodiment provides an electrochemical performance testing experiment.

[0058] The positive electrode material to be tested and acetylene black were ground and mixed, and polyvinylidene fluoride was added, wherein the mass ratio of the positive electrode material to be tested, acetylene black and polyvinylidene fluoride was 8:1:1, and they were fully mixed in a homogenizer, coated on aluminum foil, vacuum dried, and punched into 12 mm pole pieces by a cutting machine. The lithium sheet was used as the negative electrode and assembled into a 2032 button battery.

[0059] In this embodiment, the composite lithium-rich positive electrode materials A to E prepared in Examples 1 to 5, the lithium-rich manganese-based positive electrode material A prepared in Example 1, and the partially ordered lithium-rich spinel positive electrode material A were used as the positive electrode materials to be tested, respectively, to prepare batteries A to G, and the batteries A to G were subjected to constant current charge and discharge tests, with the test voltage being 2.0 to 4.8 V. The test results shown in Table 1 were obtained.

[0060] Table 1 Electrochemical performance test results of batteries A to G (mAh·g -1 )

[0061]

[0062]

[0063] It can be seen from Table 1 that the specific capacity of batteries A to E is significantly better than that of battery G. The composite lithium-rich positive electrode materials A to E can further improve the specific capacity of the positive electrode side on the basis of the original lithium-rich manganese-based oxide materials through the lithium-rich manganese / spinel-like phase composite strategy, and have good cycle performance.

[0064] Example 7

[0065] This embodiment provides a tap density test experiment.

[0066] Weigh the positive electrode material to be tested, then transfer it to the tapping measuring cylinder, fix the tapping measuring cylinder, continuously vibrate the tapping measuring cylinder 3000 times, remove the tapping measuring cylinder, read the volume information, and calculate the tap density according to the formula ρ = m / v, where ρ is the tap density in g cm -3 ; m is the mass of the positive electrode material to be tested, in g; v is the volume after compaction, in cm 3 .

[0067] In this embodiment, the composite lithium-rich positive electrode materials A to E prepared in Examples 1 to 5, the lithium-rich manganese-based positive electrode material A prepared in Example 1, and the partially ordered lithium-rich spinel positive electrode material A are used as the positive electrode materials to be tested to measure their tap densities, and the test results shown in Table 2 are obtained.

[0068] Table 2 Tap density results of each material

[0069] Material Tap density Composite lithium-rich cathode material A 1.52 Composite lithium-rich cathode material B 1.35 Composite lithium-rich cathode material C 1.43 Composite lithium-rich cathode material D 1.48 Composite lithium-rich cathode material E 1.75 Lithium-rich manganese-based positive electrode material A 1.25 Partially ordered lithium-rich spinel cathode material A 1.95

[0070] It can be seen from Table 2 that by forming a phase-composite and particle-graded ultra-high specific capacity composite positive electrode material system with partially ordered lithium-rich spinel positive electrode materials and lithium-rich manganese-based positive electrode materials, the tap density of the material can be further improved on the basis of the original lithium-rich manganese-based oxide material.

[0071] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0072] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A multiphase lithium-rich cathode material, characterized in that: The invention comprises the following components: a lithium-rich manganese-based positive electrode material and a partially ordered lithium-rich spinel positive electrode material in a mass ratio of 1 to 20:1; Wherein, the particle size of the lithium-rich manganese-based positive electrode material is 1 to 20 μm, and the particle size of the partially ordered lithium-rich spinel positive electrode material is 50 to 500 nm.

2. The multiphase lithium-rich cathode material according to claim 1, characterized in that: The lithium-rich manganese-based positive electrode material is Li 1+x M 1-x O2, wherein M is one or a combination of Mn, Ni, and Co, and 0≤x≤1; The partially ordered lithium-rich spinel positive electrode material is Li 1.4+y Mn 1.6 O 4-z F z , among which, 0.07≤y≤0.6, 0.3≤z≤0.

6.

3. A method for preparing a multiphase lithium-rich cathode material, characterized in that: The raw material components are mixed in proportion according to the formula components contained in the multiphase lithium-rich positive electrode material according to any one of claims 1 to 2, and high-energy ball milling operation is performed to obtain the multiphase lithium-rich positive electrode material.

4. The preparation method according to claim 3, characterized in that: The high energy ball milling is dry milling or wet milling using anhydrous ethanol as solvent; And / or, the conditions of the high energy ball milling are a rotation speed of 100 to 600 rpm and a duration of 2 to 24 hours; And / or, the ball-to-material ratio of the high-energy ball mill is 1.5 to 25:

1.

5. The preparation method according to claim 3, characterized in that: The preparation process of the lithium-rich manganese-based positive electrode material comprises the following steps: After dissolving the M source in pure water, adding Na2CO3 solution, adding a pH adjuster to adjust the pH to 7.5-9, stirring for 4-24 hours in an oxygen-free atmosphere, filtering the precipitate, washing, drying, and grinding, respectively, to obtain a carbonate precursor, wherein the M source is one or a combination of a nickel source, a cobalt source, and a manganese source; The carbonate precursor and the lithium source are mixed, pre-sintered at 400-600° C., sintered at 700-900° C., and cooled to room temperature to obtain the lithium-rich manganese-based positive electrode material.

6. The preparation method according to claim 5, characterized in that: The pH regulator includes one or a combination of ammonia water and ammonium bicarbonate; And / or, the oxygen-free atmosphere is a nitrogen atmosphere or an argon atmosphere; And / or, the drying conditions are: temperature 100-150° C., duration 12-24 h; And / or, the pre-sintering time is 4 to 8 hours; And / or, the sintering time is 6 to 18 hours.

7. The method according to claim 5, characterized in that The nickel source is one or a combination of Ni(CH3COO)2·4H2O, NiSO4 and Ni(NO3)2·6H2O; The cobalt source is one or a combination of Co(CH3COO)2·4H2O, CoSO4 and Co(NO3)2·6H2O; The manganese source is one or a combination of Mn(CH3COO)2·4H2O, MnSO4 and Mn(NO3)2·4H2O; The lithium source is one or a combination of LiOOCCH3, Li2CO3, LiNO3 and LiOH·H2O.

8. Use of the multiphase lithium-rich cathode material according to any one of claims 1 to 2 or the multiphase lithium-rich cathode material prepared by the preparation method according to any one of claims 3 to 7 in a lithium-ion battery.

9. A lithium ion battery, characterized in that: The composite lithium-rich cathode material according to any one of claims 1 to 2 or the composite lithium-rich cathode material prepared by the preparation method according to any one of claims 3 to 7 is used as the cathode active material.

10. The lithium ion battery according to claim 9, characterized in that: The preparation process of the positive electrode includes the following steps: The composite lithium-rich positive electrode material according to any one of claims 1 to 2 or the composite lithium-rich positive electrode material prepared by the preparation method according to any one of claims 3 to 7, conductive agent black and solvent are mixed and coated on the current collector, and dried to obtain the positive electrode of the lithium ion battery.

Citation Information

Patent Citations

  • Core-shell isomerous lithium ion battery composite positive electrode material formed by layered lithium-rich manganese base and spinel type lithium manganate and preparation method of positive electrode material

    CN107086298A

  • Mixed lithium-rich positive electrode material and preparation method and application thereof

    CN113690414A

  • Composite lithium-rich manganese-based positive electrode material of lithium ion battery and preparation method of composite lithium-rich manganese-based positive electrode material

    CN114156463A

  • Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery

    US20160028074A1

  • Lithium-rich manganese-based anode material and preparation method therefor

    WO2024174339A1

Cited By

  • Lithium-rich manganese-based positive electrode material with gradient buffer layer, preparation method of lithium-rich manganese-based positive electrode material and all-solid-state battery

    CN121506924A